2018
DOI: 10.17219/acem/64937
|View full text |Cite
|
Sign up to set email alerts
|

The correlation between pancreatic dysfunction markers and selected indices of periodontitis

Abstract: Background. Periodontitis is a major risk factor of systemic diseases with inflammatory etiology. Numerous studies have established the connection between periodontal condition and diabetes, but there are no reports in the literature on the relationship between periodontitis and other pancreas conditions. The activity of pancreatic enzymes is an important parameter of pancreatic damage, and is also a diagnostic marker of acute and chronic pancreatitis, and the bleeding index determines the periodontitis activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…Specifically, it has been investigated the role of the Gram-negative periodontal pathogen FN, an opportunistic pathogen agent having a specific role in pathogenesis of different periodontal conditions [1], [4], [8], [9], [10], [11], [12], [13], [14], [15], [16], [17], [18], [19], [20], [21], [22], [23], [24], [25], [26], and it is increasingly recognized as an important agent of PTB. A multitude of studies has identified potential periodontal pathogens that might have a causal role in determining the risk of PTB, evaluating the combined influences of genes with intrinsic and extrinsic environmental factors [45], [46], [47], [48]. These investigations have been pivotal in providing resources for the explanation of the potential impact of microbiome dysbiosis on poor obstetric outcomes [15], [16], [17], [18], [19], [20], [21], [22], [23], [24], [25], [26].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Specifically, it has been investigated the role of the Gram-negative periodontal pathogen FN, an opportunistic pathogen agent having a specific role in pathogenesis of different periodontal conditions [1], [4], [8], [9], [10], [11], [12], [13], [14], [15], [16], [17], [18], [19], [20], [21], [22], [23], [24], [25], [26], and it is increasingly recognized as an important agent of PTB. A multitude of studies has identified potential periodontal pathogens that might have a causal role in determining the risk of PTB, evaluating the combined influences of genes with intrinsic and extrinsic environmental factors [45], [46], [47], [48]. These investigations have been pivotal in providing resources for the explanation of the potential impact of microbiome dysbiosis on poor obstetric outcomes [15], [16], [17], [18], [19], [20], [21], [22], [23], [24], [25], [26].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the extensive research intended to achieve this objective, there is still a great deal of ambiguity as to the periodontal pathogen sustain this outcome. Whereas the investigation of periodontal pathogen [21] is largely restricted to the research arena, the use of short-read sequencing approach is not well established in clinical periodontology [45], [46], [47], [48], [49], [50], [51], [52], [53], [54], [55], [56]. Through analyzing the dynamic character of the oral microbial communities and their interactions with the organism, we sought to reveal through which way the association between periodontal disease and general health is understand and interpreted, focus on the relationship between oral microbiome and pregnancy [11].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations